2021
DOI: 10.3390/jcm10030516
|View full text |Cite
|
Sign up to set email alerts
|

Serum N-Glycomics Stratifies Bacteremic Patients Infected with Different Pathogens

Abstract: Bacteremia—i.e., the presence of pathogens in the blood stream—is associated with long-term morbidity and is a potential precursor condition to life-threatening sepsis. Timely detection of bacteremia is therefore critical to reduce patient mortality, but existing methods lack precision, speed, and sensitivity to effectively stratify bacteremic patients. Herein, we tested the potential of quantitative serum N-glycomics performed using porous graphitized carbon liquid chromatography tandem mass spectrometry to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“… 51 The serum N -glycome from patients infected with Pseudomonas aeruginosa , an opportunistic gram-negative pathogen closely associated with cystic fibrosis affecting lung and liver, shows increased levels of core fucosylation (as well as decreased levels of sialylation, which will be discussed later). 52 Core fucosylation levels are also increased in advanced stages of pancreatic cancer, however the authors of that study suggested that the biological function seemed to be related to the disease itself and not to the inflammation. 53 Similar glycan profiles have been described for (auto)inflammatory diseases such as rheumatoid arthritis 54 and Crohn’s disease, 30 , 55 in which fucosylation of a tri-antennary structure, indicated as an inflammatory marker, was elevated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 51 The serum N -glycome from patients infected with Pseudomonas aeruginosa , an opportunistic gram-negative pathogen closely associated with cystic fibrosis affecting lung and liver, shows increased levels of core fucosylation (as well as decreased levels of sialylation, which will be discussed later). 52 Core fucosylation levels are also increased in advanced stages of pancreatic cancer, however the authors of that study suggested that the biological function seemed to be related to the disease itself and not to the inflammation. 53 Similar glycan profiles have been described for (auto)inflammatory diseases such as rheumatoid arthritis 54 and Crohn’s disease, 30 , 55 in which fucosylation of a tri-antennary structure, indicated as an inflammatory marker, was elevated.…”
Section: Discussionmentioning
confidence: 95%
“… 62 On the other hand, bisection was significantly higher in meningitis patients presenting with the most severe clinical outcomes. 63 Bisection also discriminates between pathogens that cause bacteremia, 52 possibly reflecting differences in their microbial-associated molecular patterns and respective strengths in activating innate immune signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of host biomarkers have been targeted to distinguish viral from bacterial infections: RNA markers, 26 , 27 , 28 , 29 host protein markers, 30 , 31 , 32 host plasma lipids, 33 and the (released) host N-glycome. 34 To the best of our knowledge, we are the first to find pathogen-specific host markers by analysis of intact glycopeptides in full plasma. We observed site-specific differences in N-glycosylation, of which several are highly significant signatures to distinguish bacterial from viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, murine studies have demonstrated a reduction in the general humoral response after LD infection as indicated by low titers of anti-viral antibodies produced post-vaccination and Bbimpaired helper T-cell mediated affinity maturation (87,95). Lastly, because the LD cohort completed 2-3 week of oral doxycycline therapy, the serum N-glycome or immune response could have been altered in part due to changes in gut flora (96,97).…”
Section: Discussionmentioning
confidence: 99%